Стиснення RGB-зображень без втрат із використанням палітри - Shportko, A. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The possibilities of RGB-image compression without losses using a palette are considered. A version of the algorithm for realization of the compression with partition of the result into a trend and noise components is described. The results of using the program developed according to the offered algorithm for compression of the images of the ACT set are presented.